Present status and diversity of small indigenous fish species (SIS) in the upper reaches of river Brahmaputra in Assam, north-eastern India - Baishya, R. A.; Basumatary, S.; Kalita, H. K.; Talukdar, B.; Dutta, A.; Sarma, D. (Indian Journal of Fisheries, 2016)
An investigation was carried out to assess the status and diversity of small indigenous species (SIS) of fish in the upper reaches of the river Brahmaputra, Assam. The study was carried out for two years from January, 2013 to December, 2014 in five prominent landing stations. A total of 52 SIS of fish belonging to 15 families and 33 genera were recorded during the study period. Cyprinidae was observed to be the most dominant family with 22 species (42.31%). According to IUCN status (2015), species like Amblyceps arunchalensis and Puntius fraseri were listed as endangered species. It has been observed that the SIS were most abundant during pre-monsoon period and least abundant during winter season in the area of the river under study. The study also revealed that the upper reaches of river Brahmaputra is fairly rich in SIS fish diversity. However, better management strategies such as controlled harvest and scientific fishing policies will ensure sustainable exploitation and conservation of SIS fish in the region.